The Non-public Stakeholders’ Participation in the Implementation of Educational Tasks as a Form of Education Policy Rationalization. The Case of Local Education Policy in Poland - Kolomycew, Anna (Socialiniai tyrimai, 2018)
The article focuses on the implementation of educational tasks in rural and urban-rural municipalities in Poland. For several years education policy has been one of the key problems of the Polish municipalities due to constantly growing costs of educational tasks. This problem particularly affects small municipalities in which education absorbs most of their budgets and which limits development opportunities of municipalities in other fields. The article presents one of possible forms of local education policy rationalization, which is the transfer of educational tasks to non-public stakeholders, with particular emphasis on social organizations. In the article, the author analyzes the most engaging form of stakeholders’ participation in education policy, which is recognized as an example of co-production of public services. Thus, the concept of co-production constitutes the theoretical framework of the article.